Towards actionable visualization for software developers. Issue 2 (8th December 2017) - Merino, Leonel; Ghafari, Mohammad; Nierstrasz, Oscar
Abstract: Abundant studies have shown that visualization is advantageous for software developers, yet adopting visualization during software development is not a common practice due to the large effort involved in finding an appropriate visualization. Developers require support to facilitate that task. Among 368 papers in SOFTVIS/VISSOFT venues, we identify 86 design study papers about the application of visualization to relieve concerns in software development. We extract from these studies the task, need, audience, data source, representation, medium, and tool, and we characterize them according to the subject, process, and problem domain. On the one hand, we support software developers to put visualization in action by mapping existing visualization techniques to particular needs from different perspectives. On the other hand, we highlight the problem domains that are overlooked in the field and need more support. Abstract : We studied the state‐of‐the‐art research that provides visualization techniques to support software development, and we investigated how well these techniques serve practitioner needs. We found that the problem domains on which visualizations have focused are different from the domains that get the most attention from practitioners. Problem domains such as rationale, contracts, and policies require more attention, while a considerable amount of work is devoted to concurrency, dependency, and architecture.